(untitled) (África, 1998)
The composition of Angola’s national identity comes along with the evolution of artistic forms. Poetry has been an instrument on construction of literature in Angola. Angola’s literature has started with journalism at the final of XIX century, has grown with the novel at our thirties years and has been properly arrived at adult life with the poetry at 50s. The totality of national literature has two pillars: the tradition of ‘oral culture’ and the literary heritage from Portuguese language. Some texts from the poets Arlindo Barbeitos and David Mestres how this conflict which solution can be at the synthesis of native (African) and inherited (Portuguese) elements. Edward Said’s Nationalism concept, applied to this case, is also discussed.